2017
DOI: 10.1111/jop.12659
|View full text |Cite
|
Sign up to set email alerts
|

The effects of icariin on wound healing of extraction sites with administration of zoledronic and dexamethasone: A rat model study

Abstract: Concurrent use of zoledronic and dexamethasone inhibits the expression of VEGF, OCN, and wound healing and increases the number of osteoclast cells, serum CTX-1, and TRACP-5b after discontinuation for 10 weeks. Icariin weakens those effects in a dose-dependent manner but does not influence the onset of BRONJ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…ROT was given by subcutaneous injection once per day at a dose of 1 mg/kg, and ICA was administrated by oral gavage. The ICA and ROT concentrations were selected according to previous studies [22,28,29]. The control group was subjected to an equivalent volume of vehicles.…”
Section: Methodsmentioning
confidence: 99%
“…ROT was given by subcutaneous injection once per day at a dose of 1 mg/kg, and ICA was administrated by oral gavage. The ICA and ROT concentrations were selected according to previous studies [22,28,29]. The control group was subjected to an equivalent volume of vehicles.…”
Section: Methodsmentioning
confidence: 99%
“…Soft tissue toxicity is one of the hypotheses explaining the pathogenesis of MRONJ and promotive effect on soft tissue healing of icarrin was noted in the present study: the area of the wound in icarrin group was significantly smaller than the untreated group. The stimulative effect of icarrin on wound healing have been confirmed by other studies 13,20,21 and this may correlate to upregulated expression of VEGF which correlates to angiogenesis, 22 activated the MEK/ERK and PI3K/Akt/eNOS‐dependent signal pathways and promoted differention of keratinocyte involved in wound healing 13,20,23 . Angiogenesis is also an important factor in bone healing 12 and studies have shown the promising effect of icarrin on bone healing via promoting angiogenesis 11,24 .…”
Section: Discussionmentioning
confidence: 73%
“…Besides, icariin has shown its promotion of angiogenesis 11 which is also important in bone defect healing 12 . And pharmaceutical effects of icariin on anti‐inflammation, protecting immune system, and promoting soft tissue healing were noted 8,13 . These effects of icariin are all related to the pathophysiology of MRONJ and indicate the potential therapeutic effect on MRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the current findings were not in agreement with other investigators whose findings revealed that the administration of dexamethasone may inhibit soft tissue healing 16 or delay extraction socket healing 29 . other researchers demonstrated that dexamethasone suppressed osteoblasts both in vivo and in vitro 9,10 .…”
Section: Discussionmentioning
confidence: 92%